1)3x+2y=12 2)3x-y=4| *3
x+2y=-4|*(-1) 2x+3y=21
3x+2y=12 9x-3y=12
-x-2y=4 2x+3y=21
2x=16 11x=33
x=8 x=3
3*8+2y=18 2*3+3y=21
2y=-6 3y=15
y=-3 y=5
3)x-y=3 4)4x+3y=10|*(2)
-x-4y=7 x-2y=-3|*3
-5y=10 8x+6y=20
y=-2 3x-6y=-9
x-(-2)=3 11x=11
x=1 x=1
1-2y=-3
-2y=-4
y=2
Объяснение:
2sin(x/2)=3sin²(x/2)
2sin(x/2)-3sin²(x/2)=0
sin(x/2) (2-3sin(x/2))=0
a) sin(x/2)=0
x/2=πk, k∈Z
x=2πk, k∈Z
b) 2-3sin(x/2)=0
-3sin(x/2)=-2
sin(x/2)=2/3
x/2=(-1)^n * arcsin(2/3)+πk, k∈Z
x=2*(-1)^n * arcsin(2/3)+2πk, k∈Z
ответ: 2πk, k∈Z;
2*(-1)^k*arcsin(2/3)+2πk, k∈Z.
2)
sin6xcosx+cos6xsinx=0.5
sin(6x+x)=0.5
sin7x=0.5
7x=(-1)^k*(π/6)+πk, k∈Z
x=(-1)^k*(π/42)+(π/7)*k, k∈Z
ответ: (-1)^k*(π/42)+(π/7)*k, k∈Z.
3)
3sinx+4sin(π/2+x)=0
3sinx+4cosx=0
a) При у=-1/2
k∈Z;
b) При у=2
k∈Z.
ответ: